2005
DOI: 10.1111/j.1460-9568.2005.04093.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ephrin‐B1 and EphB receptors during denervation‐induced plasticity in the adult mouse hippocampus

Abstract: It has been widely demonstrated that Eph receptors and their ephrin ligands play multiple pivotal roles in the development of the nervous system. However, less is known about their roles in the adult brain. Here we reported the expression of ephrin-B1 and its cognate EphB receptors in the adult mouse hippocampus at 3, 7, 15, 30 and 60 days after transections of the entorhinal afferents. In situ hybridization and immunohistochemistry showed the time-dependent up-regulation of ephrin-B1 in the denervated areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 97 publications
2
11
0
Order By: Relevance
“…While expression of ephrinB1 and ephB2 in spinal interneurons has not been reported so far, expression in the white matter has already been shown to occur following SCI and expression of ephB2 has been reported in meningeal cells and of ephrinB1 and ephBs in astrocytes [75]. We also show that both ligands are expressed in layer II-III and V of the cortex consistent with previous reports of ephB2 expression in the brain [76], [77]. EphrinB1 and ephB2 were expressed in a large proportion of all interneurons studied both before and after spinal cord injury indicating that, similar to SynCAMs, ephrinB1-ephB2 interactions might contribute to the establishment of functional synapses but are unlikely to explain the differential stabilization of synaptic contacts during post-injury remodelling.…”
Section: Discussionsupporting
confidence: 91%
“…While expression of ephrinB1 and ephB2 in spinal interneurons has not been reported so far, expression in the white matter has already been shown to occur following SCI and expression of ephB2 has been reported in meningeal cells and of ephrinB1 and ephBs in astrocytes [75]. We also show that both ligands are expressed in layer II-III and V of the cortex consistent with previous reports of ephB2 expression in the brain [76], [77]. EphrinB1 and ephB2 were expressed in a large proportion of all interneurons studied both before and after spinal cord injury indicating that, similar to SynCAMs, ephrinB1-ephB2 interactions might contribute to the establishment of functional synapses but are unlikely to explain the differential stabilization of synaptic contacts during post-injury remodelling.…”
Section: Discussionsupporting
confidence: 91%
“…The interpretation of the latter finding is unclear and may perhaps represent an attempt to compensate for the subsequent synaptic dysfunction in hAβPP swe-ind mice. In line with these results, a transient increase in EphB receptor expression within two weeks of entorhinal deafferentation in mice has been reported suggesting that, in addition to its role in synaptic plasticity in normal brain, EphB receptors may be also involved in plasticity of the lesioned adult hippocampus [53].…”
Section: Discussionsupporting
confidence: 66%
“…Recent studies have demonstrated the overexpression of ephrin/Eph in injured spinal cord,21 after denervation in the mouse hippocampus30 and in multiple sclerosis lesions,31 presumably affecting the migration and adhesion of inflammatory cells to extracellular matrix and suggesting a role of ephrin/Eph in adult neural tissue repair. Expression of ephrinB proteins and the EphB receptor in vascular and perivascular cells are currently under study because they contribute to regulation of angiogenesis in cancer,32 and enhancing angiogenesis in ocular diseases such as proliferative diabetic retinopathy and retinopathy of prematurity 33…”
Section: Discussionmentioning
confidence: 99%